(untitled) (International Journal of Food and Nutritional Sciences, 2022)
AI has been used in the e-commerce and finance sectors in order to establish standardised, reliable product quality control techniques; seek for new means of reaching and servicing consumers while keeping cheap costs; and search for new ways of reaching customers and maintaining low costs. Because of this, we have been able to provide a higher level of service to our customers, manage our supply chain in a more effective manner, increase our operating efficiency, and reduce the size of our staff. Machine learning and deep learning are two of the most prominent applications of artificial intelligence, however there are a number of other techniques to apply AI. People, businesses, and governments all utilise these models to acquire insight and base their forecasts on data in order to improve their decision-making. Models based on machine learning are now being developed for the large amounts of data that are present in the food business. This article investigates the ways in which artificial intelligence and machine learning have been used in the fields of business and finance. Increasing sales, optimising profits, predicting sales, controlling stock, avoiding theft, and optimising returns on investments are some of the most prevalent uses. Other prominent applications include preventing theft and maximizing returns on investments.